1967
DOI: 10.1126/science.157.3793.1187
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins: Localization in Subcellular Particles of Rat Cerebral Cortex

Abstract: Homogenates of rat cerebral cortex contain material corresponding to prostaglandins E(1), E(2), F(1)alpha, and F(2)alpha which are concentrated mainly in the light microsomal and mitochondrial fractions. Only the former fraction exhibits significant ability to synthesize prostaglandins E(1) and F(1)alpha from bis-homo-gamma-linolenic acid. After subfractionation of the crude mitochondrial fraction, prostaglandin E and F material is found mainly in the cholinergic and noncholinergic nerve endings. We conclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1968
1968
1998
1998

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 10 publications
1
19
1
Order By: Relevance
“…As to the possible functions of PGs in activating neural pathways between the AV3V and the AVP cells, their roles as neurotransmitters could be assumed, because PGs and specific binding sites for PGE 2 have been detected in the nerve endings and synaptic membranes of the rat brain (35,36). In the AV3V, however, cyclooxygenase-like material was found not in the pathways of nerve fibers or terminal fields, but in cell bodies and dendrites (23).…”
Section: Figure 4 Effects Of Meclofenamate (Mcl) Infusion Into the Acmentioning
confidence: 99%
“…As to the possible functions of PGs in activating neural pathways between the AV3V and the AVP cells, their roles as neurotransmitters could be assumed, because PGs and specific binding sites for PGE 2 have been detected in the nerve endings and synaptic membranes of the rat brain (35,36). In the AV3V, however, cyclooxygenase-like material was found not in the pathways of nerve fibers or terminal fields, but in cell bodies and dendrites (23).…”
Section: Figure 4 Effects Of Meclofenamate (Mcl) Infusion Into the Acmentioning
confidence: 99%
“…Most of the prostaglandins in the supernatant of homogenates of rat cerebral cortex is of the PGF type, and more than 60% of the PGF material in the total homogenate cochromatographed with PGFia (Kataoka et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is evidence that the prostaglandins may be implicated in some way with neuronal activity in the central nervous system and the detection of these sub- stances in subcellular particles derived from nerve endings (Kataoka, Ramwell & Jessup, 1967) supports this view. The present investigation was undertaken to determine whether there was any correlation between the release of prostaglandins from the cerebral cortex and the pattern of activity in the electrocorticogram.…”
mentioning
confidence: 86%
“…Endogenous prostaglandins have been identified in brain (Horton & Main, 1967b) and it has been reported that they are associated with nerve endings of the cerebral cortex (Kataoka, Ramwell & Jessup, 1967). They may be released into superfusates of the brain either spontaneously or by electrical stimulation (Coceani & Wolfe, 1965;Ramwell & Shaw, 1967;Bradley, Samuels & Shaw, 1969).…”
Section: Discussionmentioning
confidence: 99%